FABP4-mediated lipid droplet formation in Streptococcus uberis-infected macrophages supports host defence - Wan, Zhixin; Fu, Shaodong; Wang, Zhenglei; Xu, Yuanyuan; Zhou, Yuanyuan; Lin, Xinguang; Lan, Riguo; Han, Xiangan; Luo, Zhenhua; Miao, Jinfeng (BMC - Springer, 2022)
Foamy macrophages containing prominent cytoplasmic lipid droplets (LDs) are found in a variety of infectious diseases. However, their role in Streptococcus uberis-induced mastitis is unknown. Herein, we report that S. uberis infection enhances the fatty acid synthesis pathway in macrophages, resulting in a sharp increase in LD levels, accompanied by a significantly enhanced inflammatory response. This process is mediated by the involvement of fatty acid binding protein 4 (FABP4), a subtype of the fatty acid-binding protein family that plays critical roles in metabolism and inflammation. In addition, FABP4 siRNA inhibitor cell models showed that the deposition of LDs decreased, and the mRNA expression of Tnf, Il1b and Il6 was significantly downregulated after gene silencing. As a result, the bacterial load in macrophages increased. Taken together, these data demonstrate that macrophage LD formation is a host-driven component of the immune response to S. uberis. FABP4 contributes to promoting inflammation via LDs, which should be considered a new target for drug development to treat infections.
Keywords: FABP4; lipid droplets; Streptococcus uberis; bovine mastitis; inflammation